Stack-Layer Dual-Element Ultrasonic Transducer for Broadband Functional Photoacoustic Tomography - Luo, Xiaofei; Cai, Yiqi; Chen, Zeyu; Shan, Han; Sun, Xin; Lin, Qibo; Ma, Jianguo; Wang, Bo (Frontiers in Bioengineering and Biotechnology, 2021)
Current Photoacoustic tomography (PAT) approaches are based on a single-element transducer that exhibits compromised performance in clinical imaging applications. For example, vascular, tumors are likely to have complicated shapes and optical absorptions, covering relatively wide spectra in acoustic signals. The wide ultrasonic spectra make it difficult to set the detection bandwidth optimally in advance. In this work, we propose a stack-layer dual-element ultrasonic transducer for PAT. The center frequencies of the two piezoelectric elements are 3.06 MHz (99.3% bandwidth at -6dB) and 11.07 MHz (85.2% bandwidth at -6dB), respectively. This transducer bridges the sensitivity capability of ultrasound and the high contrast of optical methods in functional photoacoustic tomography. The dual-element transducer enabled multiscale analysis of the vascular network in rat brains. Using a multi-wavelength imaging scheme, the blood oxygen saturation was also detected. The preliminary results showed the great potential of broad-bandwidth functional PAT on vascular network visualization.